2013
DOI: 10.2174/18715273113129990095
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and the Polyamine System

Abstract: Suicide is a significant worldwide public health problem. Understanding the neurobiology is important as it can help us to better elucidate underlying etiological factors and provide opportunities for intervention. In recent years, many lines of research have suggested that the polyamine system may be dysregulated in suicidal behaviors. Initial research in animals provided evidence of a dysfunctional polyamine stress response system, while later work using post-mortem human brain tissue has suggested that mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 61 publications
1
20
0
1
Order By: Relevance
“…In 2010, O'Connor and colleagues reported that chronic immobilization stress altered miR-34c levels in the hippocampus of rats (O'Connor et al, 2012). Of interest, immobilization stress in rats clearly alters brain levels of polyamines, which are generally seen as a stress-response system (Gross, 2013). In our study, we found a significant up-regulation of miR-34c-5p that negatively correlates with the expression of SAT1 in the brain of depressed suicide completers.…”
Section: Discussionsupporting
confidence: 60%
“…In 2010, O'Connor and colleagues reported that chronic immobilization stress altered miR-34c levels in the hippocampus of rats (O'Connor et al, 2012). Of interest, immobilization stress in rats clearly alters brain levels of polyamines, which are generally seen as a stress-response system (Gross, 2013). In our study, we found a significant up-regulation of miR-34c-5p that negatively correlates with the expression of SAT1 in the brain of depressed suicide completers.…”
Section: Discussionsupporting
confidence: 60%
“…Recently, many lines of research have suggested the involvement of the dysregulated polyamine system in suicidal behaviours. 67 , 68 , 69 Surprisingly, we found lower arginase activities (~45% reduction, P <0.01) and a trend of reduced spermidine levels (~25% reduction) in the six suicidal cases when compared with the 14 non-suicidal schizophrenic cases ( Supplementary Figure 1 ). Although the significant positive correlation between arginase activity and the age of disease onset was maintained in the non-suicidal schizophrenic cases, such relationship was not present in the suicidal cases ( Supplementary Figure 1 ).…”
Section: Discussionmentioning
confidence: 70%
“…Importantly, the OB efferents are primarily glutamatergic, 40 and olfactory dysfunction would likely disrupt the physiology of OB, which may subsequently contribute to excitatory-inhibitory imbalances in their target regions. In addition, L-ornithine was downregulated, accompanied by the downregulation of the mRNAs encoding Spermidine/spermine N1-acetyltransferase (SAT) and spermine oxidase (SMOX), 41 supporting a disturbance in polyamine catabolism during olfactory dysfunction.…”
Section: Discussionmentioning
confidence: 98%